Pengelolaan Aset Tetap Dalam Mewujudkan Opini Wajar Tanpa Pengecualian di Kabupaten Timor Tengah Utara - Afni Nooraini; Chatarina De Ricci R. Mamulak; Marja Sinurat (Institut Pemerintahan Dalam Negeri (IPDN) Kampus Sumatera Barat, 2022)
The Regional Government Financial Reports (LKPD) of Timor Tengah Utara Regency for the last five years have always received a Fair Opinion with an Exception (WDP) due to several factors, namely the insufficient management of fixed assets. This study aims to determine the management of fixed assets, inhibiting factors and supporting factors in the management of fixed assets as well as the efforts made to overcome obstacles so that the realization of Unqualified Opinion (WTP) can be realized. This study used descriptive qualitative method with inductive approach. Determining the information used is a purposive sampling technique. Data collection techniques were carried out by interview, observation, and documentation. The results show that the management of fixed assets in Timor Tengah Utara Regency has not been implemented optimally because there are several obstacles, incomplete asset acquisition documents, lack of human resources competence in running SIMDA BMD and the application of Accrual-Based Government Accounting Standards and problematic SIMDA BMD network connections. The supporting factors in the implementation of fixed asset management are adequate human resources development policies, reports on the results of BMD procurement running well and adequate supporting tools. Efforts are being made, among others: completing fixed asset documents and processing fixed assets correctly, submitting a lost fixed asset to MP TP-TGR, increasing competence for human resources and implementing the SIMDA BMD application that can be integrated into all OPDs in Timor Tengah Utara Regency.